Increased risk for primary liver cancer among women exposed to solvents. - Hernberg, Sven; Kauppinen, Timo; Riala, Riitta; Korkala, M. L.; Asikainen, U. (Scandinavian Journal of Work, Environment & Health, 1988)
An earlier case-referent study by the same authors [Int Arch Occup Environ Health 54 (1984) 147-153] reported that solvent-exposed women, but not men, had an increased risk for primary liver cancer. The present study was undertaken to verify these results. The relatives of deceased patients, ie, 377 liver cancer cases, 385 coronary infarction referents, and 476 stomach cancer referents, responded to a questionnaire on past employment and potentially relevant covariables, the response rates being 71.7, 72.7, and 69.0%, respectively. The information was assessed for solvent exposure by two occupational hygienists without knowledge of the patients' diagnoses. Seven male and seven female liver cancer cases had been exposed to solvents, the odds ratio being less than 1 for the men but greater than 3 for the women irrespective of the reference group used for comparison. The results confirm the authors' earlier findings. When both materials were combined, the odds ratio was 7.8 for the female liver cancer cases as compared with the infarction referents. In the combined material, nine female liver cancer cases, two stomach cancer referents, but no infarction referent had had at least probable exposure to chlorinated hydrocarbons. Such exposure was rare among all of the men in the study. This finding may explain why the increased liver cancer risk occurred only for the women, although a sex difference in sensitivity cannot be completely ruled out.